2000
DOI: 10.1093/jac/45.1.115
|View full text |Cite
|
Sign up to set email alerts
|

Levofloxacin in vitro activity and time-kill evaluation of Stenotrophomonas maltophilia clinical isolates

Abstract: The in vitro activity of levofloxacin and eight other antimicrobial agents against 60 clinical isolates of Stenotrophomonas maltophilia was determined by an agar dilution method using 10(4) and 10(6) cfu/spot inocula. At the lower inoculum, 85.0% of the isolates were susceptible to levofloxacin but only 58.3% were susceptible to ofloxacin; at the higher inoculum, 78.3% were susceptible to levofloxacin and 36.7% to ofloxacin. In time-kill studies, levofloxacin exerted bactericidal activity within 4 h. With oflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 9 publications
1
22
0
1
Order By: Relevance
“…Co-trimoxazole, ticarcillin/clavulanate, minocycline, doxycycline, levofloxacin, and chloramphenicol have all been reported as being the most active single agent against S. maltophilia isolated from individuals with and without CF (6,9,11,18,22,27,29). Co-trimoxazole is often the drug of first choice for therapy, although increasing in vitro resistance is being reported (2,9,14). Of the patients in our study, 24.2% had co-trimoxazole-resistant S. maltophilia, and, like Valdezate et al, we also found a bimodal distribution of MICs (29).…”
Section: Discussionmentioning
confidence: 99%
“…Co-trimoxazole, ticarcillin/clavulanate, minocycline, doxycycline, levofloxacin, and chloramphenicol have all been reported as being the most active single agent against S. maltophilia isolated from individuals with and without CF (6,9,11,18,22,27,29). Co-trimoxazole is often the drug of first choice for therapy, although increasing in vitro resistance is being reported (2,9,14). Of the patients in our study, 24.2% had co-trimoxazole-resistant S. maltophilia, and, like Valdezate et al, we also found a bimodal distribution of MICs (29).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in Spain, Canada and Latin America, authors reported that 2% of isolates of S. maltophilia were resistant to SXT [53] [54] [49], 10% in Europe [49]. Whereas an Italian study reported the highest levels of resistance reached 80.9% of the isolates [55]. Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…S. maltophilia'nın etken olduğu infeksiyonlarda kinolonlar tek başlarına ya da diğer antibiyotiklerle kombinasyon yapılarak tedavi alternatifi olmuşlardır (17). Kinolonların bu bakteriye etkinliğinin araştırıldığı çalışmalarda siprofloksasine oldukça değişken duyarlılık oranları (%25-79) bildirilmekte (7,11) ve yeni kinolonların (levofloksasin, moksifloksasin, klinafloksasin gibi) daha iyi in-vitro aktiviteye sahip olduğu belirtilmektedir (1,12,17,18). Schmitz (11) ve Hoban'ın (19) çalışmalarında ise bu bakterinin levofloksasin ve ofloksasine siprofloksasinden daha yüksek duyarlılık oranlarına sahip olduğu gösterilmiştir.…”
unclassified